Florence Nightingale : an introduction to her life and family - Nightingale, Florence, 1820-1910.; McDonald, Lynn, 1940- (Waterloo, Ont. : Wilfrid Laurier University Press, 2001)
Florence Nightingale: An Introduction to Her Life and Family introduces the Collected Works by giving an overview of Nightingale's life and the faith that guided it and by outlining the main social reform concerns on which she worked from her call to service at age sixteen to old age. This volume reports correspondence (selected from the thousands of surviving letters) with her mother, father and sister and a wide extended family. There is material on Nightingale's domestic arrangements, from recipes, cat care and relations with servants to her contributions to charities, church and social reform causes. Much new and original material comes to light, and a remarkably different portrait of Nightingale, one with a more nuanced view of her family relationships, emerges.
An outline of Florence Nightingale's life : Faith and church ; Early writing: Suggestions for thought (1852-60) ; Celibacy and suitors ; First work in nursing: Harley Street (1853-54) ; The Crimean War (1854-56) ; First royal commission, on the army (1856-59) ; Illness and invalidism ; Second royal commission, on India (1858-63) ; Working style (1859-99) ; Opposition to registration of nurses (1887-94) ; Domestic arrangements and expenditures ; Friends ; The arts ; Love of nature and companion animals ; Death rituals ; Last days, will and death -- Themes : Law, probability and application ; Positivism and idealism ; Theology/Theodikè ; Natural science ; The Italian connection ; Government and politics ; The family and individuals ; Social class and caste ; Gender roles and status of women ; Empire and imperialism ; War and militarism ; Approach to health care -- Key to editing -- Family life : Nightingale's "Lebenslauf" for Kaiserswerth ; Notes on her parents and sister -- Letters to, from and about Nightingale's immediate family : Mother, Frances "Fanny" Nightingale ; Father, W.E. Nightingale ; Sister, Parthenope, Lady Verney -- Letters to, from and about Nightingale's extended family : Grandmother, Mary Shore ; The Bonham Carter family ; The Nicholson family ; The Smith family ; The Verney family ; Godchildren and namesakes -- Domestic arrangements : Food orders and recipes ; Expenditures and donations ; Cat care ; Letters to, for and about domestic employees ; "Waifs and strays" -- Appendixes : A. Biographical sketches: The Nightingale family ; The Shore family ; The Smith family ; Father: William Edward Nightingale (1794-1874) ; Mother: Frances (Fanny) Nightingale (1788-1880) ; Sister: Frances Parthenope, Lady Verney (1819-90) ; Uncle Samuel and Aunt Mary Shore Smith ; (Sir) Harry Verney (1801-94) ; Edmund Hope Verney (1838-1910) and Margaret Verney (1844-1930) ; Blanche Smith, Arthur Hugh Clough and Arthur Clough -- B. The rise and fall of Florence Nightingale's reputation -- C. Florence Nightingale's family tree -- D. Florence Nightingale's last will and codicils.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Nightingale, Florence, -- 1820-1910.; Nightingale, Florence, -- 1820-1910.; Nightingale, Florence, -- 1820-1910.; Nightingale, Florence, -- 1820-1910.; Nightingale, Florence, -- 1820-1910; Nurses -- England -- Biography; Nursing; Philosophy; Public health; History of Nursing; 1800s.; Nurses; Philosophy; Public Health; England; Infirmières -- Angleterre -- Biographies; Soins infirmiers; Philosophie; Santé publique; nurses; nursing (health science); philosophy; public health; MEDICAL -- Nursing -- Medical & Surgical; BIOGRAPHY & AUTOBIOGRAPHY -- Medical; MEDICAL -- Nursing -- Reference; Nurses; England; Biography; Biography; Fulltext; Historical Works; Internet Resources; Biography, Collective; Plates; collective biographies; Biographies; Biographies; Biographies